2020
DOI: 10.1371/journal.pntd.0008886
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics of ivermectin for the treatment of scabies in Indigenous Australian children

Abstract: Ivermectin is a broad-spectrum antiparasitic agent used for the treatment and control of neglected tropical diseases. In Australia, ivermectin is primarily used for scabies and is licensed in children aged ≥5 years weighing >15 kg. However, young children, aged <5 years, are particularly vulnerable to scabies and its secondary complications. Therefore, this study aimed to determine an appropriate ivermectin dose for children aged 2 to 4 years and weighing ≤15 kg. We conducted a prospective, pharmacokinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Recommendation of a weight-based oral dosage of IVM assumes that plasma clearance is directly proportional to Total Body Weight (TBW), regardless of body composition. This is supported by several population pharmacokinetic investigations, which have shown that body weight is the relevant covariate (Schulz et al, 2019;Gwee et al, 2020). In a small, homogeneous trial, which enrolled 12 healthy volunteers, only BW was a significant covariate for plasma clearance and volume of distribution, while the Body Mass Index (from 18.1 to 26.4 kg/square meter) was not significant (Duthaler et al, 2019).…”
Section: Discussionmentioning
confidence: 78%
“…Recommendation of a weight-based oral dosage of IVM assumes that plasma clearance is directly proportional to Total Body Weight (TBW), regardless of body composition. This is supported by several population pharmacokinetic investigations, which have shown that body weight is the relevant covariate (Schulz et al, 2019;Gwee et al, 2020). In a small, homogeneous trial, which enrolled 12 healthy volunteers, only BW was a significant covariate for plasma clearance and volume of distribution, while the Body Mass Index (from 18.1 to 26.4 kg/square meter) was not significant (Duthaler et al, 2019).…”
Section: Discussionmentioning
confidence: 78%
“…This strategy has shown its effectiveness in koranic schools in Bangladesh. The best results with ivermectin have been obtained in trials carried out on islands -poorer results, including Australia, have been seen in land-based or city settings (Gwee et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It is effective in onchocerciasis; the disease caused by the Loa loa nematode and in lymphatic filariasis [ 32 ]. It is used to treat and control soil-transmitted helminths, strongyloidiasis [ 33 ]. In Australia, the substance is also approved for the treatment of scabies.…”
Section: Currently Used Drugs With Newly Discovered Antiparasitic Pro...mentioning
confidence: 99%